If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(v + 3) + -2v = 2(3v + 4) + -13 Reorder the terms: 8(3 + v) + -2v = 2(3v + 4) + -13 (3 * 8 + v * 8) + -2v = 2(3v + 4) + -13 (24 + 8v) + -2v = 2(3v + 4) + -13 Combine like terms: 8v + -2v = 6v 24 + 6v = 2(3v + 4) + -13 Reorder the terms: 24 + 6v = 2(4 + 3v) + -13 24 + 6v = (4 * 2 + 3v * 2) + -13 24 + 6v = (8 + 6v) + -13 Reorder the terms: 24 + 6v = 8 + -13 + 6v Combine like terms: 8 + -13 = -5 24 + 6v = -5 + 6v Add '-6v' to each side of the equation. 24 + 6v + -6v = -5 + 6v + -6v Combine like terms: 6v + -6v = 0 24 + 0 = -5 + 6v + -6v 24 = -5 + 6v + -6v Combine like terms: 6v + -6v = 0 24 = -5 + 0 24 = -5 Solving 24 = -5 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2x^2-2x-6=x^2-x-4 | | f+8squared=3squared | | x-13x=3x-6 | | 36=12x+x^2 | | y=-x+6x-12 | | a(5)=6 | | 3+11x-1=9x+29-7x | | 4.9x-10x/3-12 | | 12x=9x+342 | | 8x+19=6x+34 | | 5x^2+17x-17=3-4x | | (14x^7-16x^3)/2x^3 | | x+(x*.22)=275 | | 4X+43=2X+69 | | (2*x-10/3)*(5/6*x-30) | | (2x-10/3)x(5/6x-30) | | 26x=64 | | (3v-7)(5-v)=0 | | (7x^2+2)(4x^2-19x-5)=0 | | 5k-10/12/6k | | 4(5x-4)+6=-4 | | 4h=220m | | (2x+3)(3x^2-13x+12)=0 | | y=6-2/3y | | 220m=4h | | 25x^2+14x+49=0 | | V/18=u | | 5x-55=6x-42 | | 2/3(1/2x+12)=1/2(1/3x+14)-3 | | -2(x)=-6 | | 32-5/8=x | | 32-4/8=x |